2008
DOI: 10.1242/jcs.035758
|View full text |Cite
|
Sign up to set email alerts
|

AQP4 knockout impairs proliferation, migration and neuronal differentiation of adult neural stem cells

Abstract: 2+channel CaV1.2 subtype in ANSCs. Together, these findings suggest that AQP4 plays a crucial role in regulating the proliferation, migration and differentiation of ANSCs, and this function of AQP4 is probably mediated by its action on intracellular Ca 2+ dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 81 publications
7
123
0
Order By: Relevance
“…For instance, we reported that cells with endogenous or exogenous, stable or transient, expression of AQP3 treated with Auphen, a potent inhibitor of the glycerol permeability of AQP3, 59 were arrested in the S-G2/M phases of the cell cycle, suggesting the possibility that the inhibition of AQP3 permeability somehow detains the progression of the cell cycle, thereby slowing cell proliferation. 18 In agreement with our results others have found that cell cycle of neurospheres derived from adult neuron stem cells of the subventricular zone (SVZ) in AQP4 knockout mice get arrested at the G2-M stage, 87 functionally implicating AQP4 in the activation and differentiation of the mice SVZ neurogenic niche.…”
Section: Cell Cycle and Aqpssupporting
confidence: 92%
See 2 more Smart Citations
“…For instance, we reported that cells with endogenous or exogenous, stable or transient, expression of AQP3 treated with Auphen, a potent inhibitor of the glycerol permeability of AQP3, 59 were arrested in the S-G2/M phases of the cell cycle, suggesting the possibility that the inhibition of AQP3 permeability somehow detains the progression of the cell cycle, thereby slowing cell proliferation. 18 In agreement with our results others have found that cell cycle of neurospheres derived from adult neuron stem cells of the subventricular zone (SVZ) in AQP4 knockout mice get arrested at the G2-M stage, 87 functionally implicating AQP4 in the activation and differentiation of the mice SVZ neurogenic niche.…”
Section: Cell Cycle and Aqpssupporting
confidence: 92%
“…In contrast, overexpression of AQP1, AQP8 and AQP9 was observed after lactacystin treatment. [126][127][128] However, favoring a role for AQP4 in apoptosis, Kong et al 87 observed increased basal apoptosis in adult neural stem cells obtained from KO AQP4 ¡/¡ mice.…”
Section: Apoptosis and Aqpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, spontaneous repetitive Ca 2þ spikes may arise in human mesenchymal stem cells (HMSCs) [30,58], adult mice neural stem cells [59], and human cardiac progenitor cells (HCPCs) [60]. Similar to VEGF-induced Ca 2þ waves in ECFCs, the oscillatory response to serum as well as the spontaneous Ca 2þ transients in HMSCs [30] were shaped by the interplay between InsP 3 -dependent Ca 2þ release and SOCE [43,44,57].…”
Section: Discussionmentioning
confidence: 99%
“…70 Aquaporin-4, responsible for water and ion homeostasis in the central nervous system, is also expressed in NSCs and plays important roles in the proliferation, survival, migration and neuronal differentiation of adult VZ NSCs via modulation of intracellular Ca 2+ dynamics. 71 Highly selective pharmacological tools are still lacking for these particular large pore-type channels. Their usefulness as therapeutic targets must therefore be put on hold until such tools are discovered.…”
Section: Involvement Of Other Types Of Channelsmentioning
confidence: 99%